Erythrocyte Oxidative Stress Markers in Children: A Clinical Laboratory Experience - Hermann, Priscila Bacarin; Henneberg, Railson; Nascimento, Aguinaldo José do; Leonart, Maria Suely Soares (Journal of Pediatric Biochemistry, 2015)
Because oxidative damage to erythrocytes plays an important pathophysiologic role in many diseases and there are some difficulties in obtaining reference intervals for children in many laboratory tests, this work intends to describe the determination of oxidative stress parameters and the results obtained for children. A total of 280 blood samples were obtained from children between 8 and 11 years old, without any hematological disease. Samples were analyzed for seven oxidative stress parameters, methemoglobin, reduced glutathione, TBARS, percentage of hemolysis and activity of the enzymes G6PD, superoxide dismutase, and catalase. To draw a comparison, the same parameters were analyzed in children with sickle cell disease. Because all results presented normal distribution in the Kolmogorov-Smirnov, data were expressed as 2.5 and 97.5th accumulated percentiles and the statistical analysis between male and female children was performed using Student t-test. A p value <0.05 was considered significant. Except for hemolysis, no significant difference was observed on oxidative stress parameters, in normal children, separated by sex. Except for reduced glutathione and superoxide dismutase, significant differences were observed in all parameters between normal children and those with sickle cell disease. Oxidative stress parameters can be determined in children using simple laboratory methods with small volumes of blood and the establishment of reference intervals is necessary to improve clinical decisions.
Keywords: reference intervals; oxidative stress; children